Analisis Kandungan Logam Timbal (Pb) Pada Air Dan Ikan Papuyu Di Daerah Sungai Alalak Dengan Metode Spectrofotometri Serapan Atom (SSA) - Tuti Alawiyah; Rahmadani Rahmadani (LPPM Universitas Sari Mulia, 2021)
Background Alalak River is a river whose people have daily activities, these activities include drinking water sources, bathing, washing clothes, cooking, washing food ingredients. The Alak River is also a river that is surrounded by industries such as the wood playwood industry and the Pertamina industry. The existence of the factory can lead to heavy metal contamination around the river. Objective to analyze the content of lead metal in water and papuyu fish in the Alalak river area with atomic absorption spectrophotometry method Method The research method is an analytical description by identifying lead heavy metals in fish and river water using color reactions for qualitative analysis and Atomic Absorption Spectrophotometry at a wavelength of 283.3. Results : The study showed the color reaction of qualitative analysis on river water and papuyu fish meat with positive results with KI, NaOH and HCl as reagents. Fish content results. The results obtained in sample A of papuyu fish were 0.450 mg/kg and sample B of alalak river water was 0.003 mg/L, with the linear regression equation y = 0.00020 + 0.1556 x a correlation coefficient (r) of 0.998330, the sample average is 5.371 Conclusion: The conclusion of the study Contains analysis of lead levels in water and meat of papuyu fish in the Alalak River, Banjarmasin, obtained for positive qualitative test results showing lead metal compounds in all reagents. Quantitative results of lead levels in papuyu are 0.450 mg/kg